2016
DOI: 10.18632/oncotarget.12622
|View full text |Cite
|
Sign up to set email alerts
|

Low Ki67/high ATM protein expression in malignant tumors predicts favorable prognosis in a retrospective study of early stage hormone receptor positive breast cancer

Abstract: IntroductionThis study was designed to investigate the combined influence of ATM and Ki67 on clinical outcome in early stage hormone receptor positive breast cancer (ES-HPBC), particularly in patients with smaller tumors (< 4 cm) and fewer than four positive lymph nodes.Methods532 formalin-fixed paraffin-embedded specimens of resected primary breast tumors were used to construct a tissue microarray. Samples from 297 patients were suitable for final statistical analysis. We detected ATM and Ki67 proteins using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Feng et al (52) reported that elevated Ki67 expression is associated with poorer prognosis in breast cancer. Shin et al (53) pointed out that high Ki67 reflects poor prognosis in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al (52) reported that elevated Ki67 expression is associated with poorer prognosis in breast cancer. Shin et al (53) pointed out that high Ki67 reflects poor prognosis in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 associates with cell cycle progress and the short half-life confer it an effective biomarker for assessing growth fraction of tumor cells. Ki-67 is one of the most widely used immunohistochemistry (IHC) proliferation antigen and has been confirmed as an independent predictive and prognostic factor in breast cancer [ 15 , 16 ]. Ki-67 is an important parameter in sub-classifying luminal tumors into a good prognosis luminal A subtype and a worse prognosis luminal B subtype [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of Ki-67-positive nuclei to the total number of nuclei was used as the labeling index [75]. …”
Section: Methodsmentioning
confidence: 99%
“…Five representative areas of each section were chosen to count the immunoreactive cells, and at least 200 cells from each area were evaluated (×400). The percentage of Ki-67-positive nuclei to the total number of nuclei was used as the labeling index [ 75 ].…”
Section: Methodsmentioning
confidence: 99%